Regional identity and social capital in regional economic development and planning - Garri Raagmaa (European Regional Science Association (ERSA), 2001)
This paper analyses the regional/local institutionalisation and social capital formation process and its components. The focus is on regional identity - the special kind of phenomenon, which forms throughout historical and territorial socialisation. The great ambition of this paper is to interrelate Anssi Paasi (1986) and other cultural geographers' and sociologists' ideas with recent regional economic development and planning discussion and to enhance the currently very popular participatory approach to regional identity as a planning tool. The theoretical part describes components and the process of regional identity formation. It analyses its positive and negative effects in regional economic development. We assume that regional identity correlates with people's volition in achieving common goals and raises their personal activity and influences due to the regional economic development and planning process. The regional identity is hypothetically crucial in securing public participation in planning too. The main empirical part of the chapter is based on mass survey (carried out simultaneously in three communities) analysis and serves as test for the hypothesises that arise from theoretical discussion. Key words: regional identity%2C institutionalisation, public participation
Keywords: 330